Structural adjustment and changes to employment use in Japan - DeStefano, Timothy (OECD Publishing, 2020)
This paper examines the determinants of structural adjustment in Japan and identifies several factors that explain the use of certain employment types. Its findings are based on a novel plant-level dataset that provides considerable detail on the types of employees used by Japanese manufacturers between 2001 and 2014. Analysis of this dataset shows that growth in the diffusion of robotics is linked to fewer non-regular employees, which seems to be partially driven by the positive association between robot adoption and the dismissal of certain types of non-regular workers. It also finds that offshoring from Japan to other countries contributes to the use of both regular and non-regular workers, while higher plant productivity is related to the use of more regular workers. Finally, establishments that experienced job dismissals appear to substitute non-regular workers for regular workers
Keywords: Science and Technology; Japan